2003
DOI: 10.1142/s0218810403001443
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Scapholunate Dissociation: Ligamentous Repair Associated with Modified Dorsal Capsulodesis

Abstract: We previously reported that our repair and/or reconstruction of the scapholunate interosseous ligament reduced the scapholunate dissociation and improved the clinical results. Re-evaluation of these patients after three years revealed that malrotation of the scaphoid advanced significantly although the clinical results declined only slightly. To prevent progression of scaphoid malrotation, a modified dorsal capsulodesis was subsequently added to the ligamentous repair of scapholunate dissociation. The records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The SLIL is secured with horizontal mattress sutures [2,3]. Minami and Kaneda [32] reported on 12 direct SLIL repairs at a mean follow-up of 5 years and reevaluated those 3 years later [33]. The authors found deterioration of the clinical outcome as well as an increase in the SL angle from 50°to 60°.…”
Section: Stage 2: Complete Disruption With Repairable Ligamentmentioning
confidence: 99%
“…The SLIL is secured with horizontal mattress sutures [2,3]. Minami and Kaneda [32] reported on 12 direct SLIL repairs at a mean follow-up of 5 years and reevaluated those 3 years later [33]. The authors found deterioration of the clinical outcome as well as an increase in the SL angle from 50°to 60°.…”
Section: Stage 2: Complete Disruption With Repairable Ligamentmentioning
confidence: 99%
“…Some of the techniques used today include repair of the SLIL, screw reduction, debridement, capsulodesis, tenodesis, bone-tissue-bone fixation, and combinations thereof. [7][8][9][10][11][12][13][14][15] The single most common surgical procedure performed for chronic SL instability with an irreparable SLIL without osteoarthritis in the United States and Canada is the Blatt capsulodesis (BC). 16 In 1987, Blatt described a dorsal capsulodesis to correct the excessive scaphoid flexion associated with SL dissociation.…”
mentioning
confidence: 99%
“…The literature suggests that the most beneficial treatment for scapholunate dissociation is an early repair of the scapholunate interosseous ligament, which occurred in this case. 5 Although positive outcomes after lunate dislocations require a timely diagnosis and immediate surgical intervention, the extent of cartilage damage or associated wrist complex trauma may complicate recovery.…”
Section: Resultsmentioning
confidence: 99%